ANALISIS KELAYAKAN FINANSIAL USAHA PENGOLAHAN IKAN SALAI PATIN SYSTEM LIQUID SMOKE (ASAP CAIR) (Studi Kasus Industri Rumah Tangga Senaning Jaya Di Desa Senaning Kecamatan Pemayung Kabupaten Batanghari) - Asmaida Asmaida (Universitas Batanghari Jambi, 2011)
Research methods in data collection using the method of census, which collected data includes primary data and secondary data. The type of data used are time series data (time series). Determination of Domestic Industry Senaning Jaya as study sites were purposively selected (purposive).Methods of data analysis used to answer the purpose of this research is to use indicators Break Even Point (BEP) for volume production and prices, Benefit Cost Ratio (B / C), Net Present Value (NPV), and Payback Period of Capital (PPC) .The result showed that the fish processing business system, liquid smoke smoked catfish Indusrti Household Senaning diusakan Jaya profitable or feasible. This can be seen from the BEP production volume is 956.1 kg, shall mean this business will achieve the BEP when has produced 956.1 kg of smoked fish, catfish. While the value of BEP production price is USD. 33 536, - per kg, shall mean this business will achieve the BEP production if the selling price of at least Rp. 33 536, - per kilogram. Value B / C is 1.40, meaning that with the sacrifice of a fee of Rp.100 will generate revenue of Rp. 140. The average value of NPV for a year at an interest rate of 17% per annum obtained by Rp.21.124.056, -, this NPV shows still provide income in present value is far greater than zero, although the use of the opportunity cost of capital (opertunity cost) by 17%. PPC value is 0.69 years, meaning that the fish processing business systen liquid smoke smoked catfish is able to return the investment that is planted in this business as a whole prior to the economic life out of business.